Eleven-year summary of KSU on-farm swine testing program - David A Nichols; D S Pollmann; W G Olson (Kansas Agricultural Experiment Station Research Reports, 1982)
Records of approximately 11,000 boars and 6,000 gilts enrolled in the KSU on-farm swine test program were summarized. Both boars and gilts reached 220 lbs 5 days sooner in 1980 than 1970. Of the traits evaluated, the largest improvement was a reduction in backfat thickness of 25% from 1970 to 1980. Loin-eye area increased from 1970 to 1975 but declined from 1975 to 1980.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; KSU On-Farm Swine Testing Program